Chemometric Techniques for Enhancing UV-Vis Spectrophotometric Determination of Metal Ions: A Review - Yaseen, Suhair M.; Mahmood, Mustafa F.; Yaseen, Noor M.; Khudhair, Zahraa T. (Al-Mustansiriyah Journal of Science, 2026)
Background: Trace metal ions play vital roles in living organisms and, at higher concentrations, are important in industrial applications such as food supplement production and polymer manufacturing. Therefore, reliable analytical methods for quantifying metal ions in different samples are urgently needed. Spectrophotometry is a widely used technique for this purpose due to its simplicity, sensitivity, rapid analysis, and cost-effectiveness in pharmaceutical, environmental, and industrial fields. Objective: The simultaneous quantification of multiple analytes in a single sample hinders the classical spectrophotometric methods. To overcome issues such as matrix interference, signal noise, and the need for separation or concentration steps, chemometric techniques combined with spectrophotometry have been proposed as effective solutions. However, despite their advantages, many chemists remain partially or fully unfamiliar with these analytical approaches. Methods: The current review article aims to attract more attention to the concepts of chemometric statistical models and their applications in UV-Vis spectrophotometric determination of metal ions and drug contents, which have been recorded in international publications between 2015 and 2025. We summarized and compared the publications on metal ion determination using only classical UV-Vis spectrophotometry and by using a combination of classical and chemometric techniques; we also compared those of chemometric models for drug spectrophotometric determination. Results: During the past ten years, studies on metal ion determination using chemometric-assisted spectrophotometry represented 32.7% (17 out of 52) of the total published research. In the same period, drug-related chemometric research was about four times higher than metal studies. This difference arises because metal ion analysis usually requires complexation with organic reagents to form colored complexes, while drug determination often relies on their inherent absorption bands without complexation. Conclusions: It is essential for chemists to understand chemometric principles as a modern, essential, and advanced branch of analytical chemistry that opens many new windows for research with many benefits and great facilities.